2012
DOI: 10.1080/13546805.2011.633748
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of olfactory function in olfactory and auditory-verbal hallucinators with schizophrenia, and normal controls

Abstract: The presence of habituation deficits and past episodes of brief unconsciousness, and absence of olfactory affective impairment, have not been identified before as correlates of OHs, suggesting these factors may be worthy of further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Prevalence estimates of olfactory hallucinations have likewise varied from 6% to 35%, depending on sample characteristics or specific questions asked (Kopala et al, 1994; Longden et al, 2016; McCarthy-Jones et al, 2017). Most studies have focused on olfactory or cognitive dysfunction in the presence of olfactory hallucinations (Arguedas et al, 2012a; Arguedas et al, 2012b; Kopala et al, 1994; Stevenson et al, 2012). A single phenomenological study found that food- or fragrance-related odors were most common (Stevenson et al, 2011).…”
Section: Tactile and Olfactory Hallucinationsmentioning
confidence: 99%
“…Prevalence estimates of olfactory hallucinations have likewise varied from 6% to 35%, depending on sample characteristics or specific questions asked (Kopala et al, 1994; Longden et al, 2016; McCarthy-Jones et al, 2017). Most studies have focused on olfactory or cognitive dysfunction in the presence of olfactory hallucinations (Arguedas et al, 2012a; Arguedas et al, 2012b; Kopala et al, 1994; Stevenson et al, 2012). A single phenomenological study found that food- or fragrance-related odors were most common (Stevenson et al, 2011).…”
Section: Tactile and Olfactory Hallucinationsmentioning
confidence: 99%